The Orange Order: A Religious Institution or an Expression of Implicit Religious Spinning? - Stewart, Francis (Implicit religion, 2015)
Implicit Religion has long been utilized within academia, and religious studies in particular, as an analytical tool with which to examine and critique commonly held conceptions and iterations of what "religion" is or could be. However there is application potentiality outside of academia for Implicit Religion, and this article seeks to utilize the power of such an approach to expose the oversimplified use of traditional religious categories in regards to the Northern Irish Troubles. By applying the framework of Implicit Religion, as outlined by Edward Bailey, to the Orange Order this article seeks to demonstrate how it can provide key insights and understandings to a very complicated and confusing situation. In areas of extended conflict and civil war, religion as an identity marker is often ignored or subsumed within attempts to deal with immediate crises, disarmament and political stability. Using tools such as Implicit Religion could help to bring religion back into the wider picture of the social, political and cultural issues that surround such contexts as Northern Ireland. It should be noted, though, that this article is not arguing that the Orange Order is a form of Implicit Religion or should even be considered as a new religious movement. This article is using the tools of Implicit Religion and shining them on to the Orange Order as an example of how those tools can better reveal what is actually going on under the surface.